Relatório de estágio curricular obrigatório: estratégias de marketing como forma de superar objeções sobre produtos na área comercial veterinária - Cansan, Bibiana Susin (My University, 2024)
This work has the goal of informing the accomplished activities during the mandatory internship in Veterinary Medicine period, which happened from March 4th of 2024 until May 20th of 2024, under the orientation of the Veterinarian Fernanda Piasson Rodrigues, at Bagé Importer Corporation, having as its focus all Vetnil product line. During this period, the intern operated as technical promoter of the lab. The research was conducted through a questionnaire created at Microsoft Forms and sent to the customers, with the objective of identifying the most frequent objections about the Vetnil products. Through the research, it was possible to obtain relevant information about which were the most frequent objections. Posterior to the data collection, the study of different Marketing strategies to resolve such objections became possible, thus as identifying the most suitable ones for each different situation. It was possible to conclude, in the end of the internship period, that Marketing is a tool of great positive impact in the veterinary retail business, even though it is little explored by the professionals of this mean. On return visits to the sales points, the customers informed that with the right Marketing strategies for objection overcoming, there was a raise on the sales conversions. At the end of the internship period, it was concluded that the adopted strategies to overcome the objections presented by customers showed positive results, increasing sales and consequently the company's profit. [resumo fornecido pelo autor]
Este trabalho tem como objetivo informar as atividades realizadas durante o período de estágio curricular obrigatório em Medicina Veterinária, realizado no período de 04 de março de 2024 até dia 20 de maio de 2024, sob orientação da Médica Veterinária Fernanda Piasson Rodrigues, na Importadora Bagé S/A, tendo como foco a linha de produtos Vetnil. Durante o período, a estagiária atuou como promotora técnica do laboratório. A pesquisa foi realizada por meio de um questionário criado na plataforma Microsoft Forms e enviado aos clientes, com o objetivo de identificar as objeções mais frequentes em relação aos produtos Vetnil. Por meio da pesquisa, conseguiu-se obter as informações acerca de quais as objeções mais frequentes. Após a coleta de dados, tornou-se possível o estudo de diferentes estratégias de Marketing para sanar tais objeções, assim como identificar as mais apropriadas para as distintas situações. Conclui-se, ao fim do período de estágio, que o Marketing é uma ferramenta de grande impacto positivo no meio de vendas na área da veterinária, mesmo ainda sendo pouco explorado pelos profissionais desse âmbito. Em visitas de retorno aos pontos de venda, os clientes informaram que, com as estratégias de Marketing corretas para superação de objeção, houve um aumento na conversão de vendas. Conclui-se ao fim do período de estágio que as estratégias adotadas para a superação das objeções apresentadas pelos clientes mostraram resultado positivo, aumentando as vendas e consequentemente o lucro da empresa. [resumo fornecido pelo autor]
Keywords: Medicina veterinária; Marketing